Short-term lending: Payday loans as risk factors for anxiety, inflammation and poor health. (August 2018) - Sweet, Elizabeth; Kuzawa, Christopher W.; McDade, Thomas W.
Abstract: While research now consistently links consumer financial debt with adverse emotional health outcomes, specific forms of debt and their impact on measures of physical health are underexplored. This gap in knowledge is significant because different forms of loans and debt may have different experiential qualities. In this paper, we focus on a type of unsecured debt - short-term/payday loan borrowing – that has risen dramatically in recent decades in the United States and is characterized by predatory, discriminatory, and poorly regulated lending practices. Using data from a study of debt and health among adults in Boston, MA (n=286), we test whether short-term borrowing is associated with a range of emotional and physical health indicators. We find that short-term loans are associated with higher body mass index, waist circumference, C-reactive protein levels, and self-reported symptoms of physical health, sexual health, and anxiety, after controlling for several socio-demographic covariates. We discuss these findings within the contexts of regulatory shortcomings, psychosocial stress, and racial and economic credit disparities. We suggest that within the broader context of financial debt and health, short-term loans should be considered a specific risk to population health. Highlights: Short-term loans (STL) are associated with multiple indicators of poor health Prior research has explored general debt as a health determinant Specific types of debt, like STL, are understudied STL's predatory lending practices raise concerns for population health